The Application of Whole−Exome Sequencing in Patients With FUO - Guo, Wanru; Feng, Xuewen; Hu, Ming; Shangguan, Yanwan; Xia, Jiafeng; Hu, Wenjuan; Li, Xiaomeng; Zhang, Zunjing; Shi, Yunzhen; Xu, Kaijin (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Fever of unknown origin (FUO) is still a challenge for clinicians. Next-generation sequencing technologies, such as whole exome sequencing (WES), can be used to identify genetic defects in patients and assist in diagnosis. In this study, we investigated the application of WES in individuals with FUO. Methods: We performed whole-exome sequencing on 15 FUO patients. Clinical information was extracted from the hospital information system. Results: In 7/15 samples, we found positive results, including potentially causative mutations across eight different genes: CFTR, CD209, IRF2BP2, ADGRV 1, TYK2, MEFV, THBD and GATA2. Conclusions: Our results show that whole-exome sequencing can promote the genetic diagnosis and treatment of patients with FUO.